Mania : a novel [large type] - Shriver, Lionel (Harper Large Print, an imprint of HarperCollins Publishers, 2024)
In an alternative 2011, the Mental Parity movement takes hold. Americans now embrace the sacred, universal truth that there is no such thing as variable human intelligence. Because everyone is equally smart, discrimination against purportedly dumb people is "the last great civil rights fight." Tests, grades, and employment qualifications are all discarded. Children are expelled for saying the S-word ("stupid") and encouraged to report parents who use it at home. A college English instructor, the constitutionally rebellious Pearson Converse rejected her restrictive Jehovah's Witness upbringing as a teenager, and so has an aversion to dogma of any kind. Made impotent in the university classroom, she's also enraged by the crushing of her exceptionally bright children's spirits in primary school. Fortunately, she enjoys the confidence of a best friend, a media commentator with whom she can speak frankly about her socially unacceptable contempt for the MP movement. Or at least she thinks she can... until one day the political chasm between the two women becomes uncrossable, and a lifelong relationship implodes.